Analisis Kebutuhan Media Layanan Bimbingan dan Konseling untuk Menguatkan Penghargaan Diri Siswa SMP - Charisma Daniyah; Wiryo Nuryono (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to analyze the requirements of guidance and counseling services for innovative service tools in line with student characteristics. Methods – This study employed a descriptive qualitative research approach. Data was collected through observation, interviews with guidance and counseling teachers, and the distribution of questionnaires to 123 students. The study involved direct observation of guidance and counseling activities; interviews were conducted with three guidance counselors, each lasting 40-47 minutes. The instruments used included a media needs questionnaire and a self-esteem questionnaire. The data were analyzed using descriptive percentage techniques to describe students’ needs regarding guidance and counseling services. Findings – The results of the study indicate that the use of media in guidance and counseling services remains limited to simple media such as PowerPoint and lecture methods. Meanwhile, the needs analysis revealed that students require more diverse media, with the percentage of needs for augmented reality media at 70%, animation media at 67%, digital media at 65%, inclusive media at 66%, and contextual media at 56%. Additionally, the results of the self-esteem analysis indicate variations across each measured aspect, suggesting that students’ self-esteem levels are not uniform.Research Implications – This study suggests that guidance and counseling services should consider utilizing a wider variety of technology-based media tailored to students’ needs. However, this study has limitations regarding the implementation and effectiveness of such media in practice. Therefore, future research is expected to develop and evaluate the use of technology-based guidance and counseling media in a broader context.